EDUKASI PENCEGAHAN CACINGAN SEBAGAI IMPLEMENTASI PROGRAM GENERASI SADAR STUNTING : EDUKASI PENCEGAHAN CACINGAN SEBAGAI IMPLEMENTASI PROGRAM GENERASI SADAR STUNTING (STIKes Mitra Keluarga, 2022)
Referring to the problem, the impact of worms related to stunting, it is necessary to undertake community service activities (CSA) regarding education on the prevention and treatment of intestinal worms as the implementation of the stunting awareness generation program. This community service activity aims to equalize understanding and provide knowledge about the prevention and treatment of intestinal worms that are integrated with the stunting program. The method of implementing this activity is carried out online in the form of a webinar using the Zoom Meeting application. The target audience includes high school/vocational high school students, students, teachers, lecturers, and health workers. CSA implementation includes preparation (producing materials and publication flyers), implementation (exposure to materials on prevention and treatment of intestinal worms in children), and evaluation (pre-test and posttest assessments). The realization of this activity showed the number of participants was 117 which included 104 students, 10 health workers, and 3 housewives. The indicators for the success of this activity are indicated by the increase in the average score from the pre-test of 63.19 to the post-test of 74.86 with a percentage increase in knowledge of the prevention and treatment of intestinal worms by 16%. This CSA concludes that participants can understand the material on prevention and knowledge of worms. The recommendation from this activity is that it is necessary to carry out direct follow-up activities in worm-endemic areas in the form of treatment measures, prevention programs, and periodic monitoring in worm-endemic areas in collaboration with local health centers.